The Problem of Diversion in Children Perpetrators of Traffic Violations in Indonesia - Prasetyono, Lafri (Universitas Negeri Gorontalo, 2022)
Children as perpetrators of traffic accidents that cause fatalities, this is one of the classic problems related to the application of the legal system and its functionalization by law enforcement officials in Indonesia. How is the protection of children in the juvenile criminal justice system related to the Diversion Problems in Children Traffic Violators in Indonesia? Regarding the Criminal Code and Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation and Law Number 11 of 2012 concerning the Juvenile Justice System as regulated in Article 1 paragraph (7), Article 12, Article 52 verse 5. The results of the research found that there are still disparities (differences) in the law enforcement process in Indonesia for children as traffic offenders and other findings related to diversion techniques are found in the Indonesian Police Criminal Investigation Unit No. Pol.: TR/1124/XI/2006 which provides instructions and rules that can refer to the completion of diversion efforts. Diversion efforts at the level of investigation related to Law no. 11 of 2012 concerning the Criminal Justice System, the prosecution and examination of children's cases in district courts have not been implemented optimally so it is recommended that at the level of investigation, prosecution, and examination of children's cases in district courts it is advisable to make diversion efforts.